Significance of Cheiloscopy and Dermatoglyphics in Sex Determination - V.Anu1 , P.Lokeswari2, S.Madhumitra2 , S.Lavanya2 , C.Lavanya2 , K.Madhumitha2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Personal identification has an important role in forensic sciences. Lip print and thumb print can be used for personal identification since they are unique for individuals and do not change during the life of a person. Objective: To analyse predominant patterns of lip print in females and males, To analyse predominant patterns of finger print in females and males, To identify if there exists any correlation between lip prints and finger prints. Material and Method: A cross sectional study was conducted in Sathyabama Dental College among 500 individuals (250 females and 250 males) between age group of 18-40 years. Fingerprint and lip print of all the subjects were collected and compared, and the results were analyzed based on Micheal Kucken classification system for fingerprints and Suzuki and Tsuchihashi classification for lip prints. Descriptive and inferential statistics were carried out. Level of significance was set as 0.05. Result: Reticular lip print pattern was found in majority (36.4%) of the males, whereas vertical grooves (29.6%) and branched grooves (29.6%) are common in females. Finger prints showed that loop pattern is more common in both males and females. This study showed a significant correlation between lip prints and thumb pattern in males while females showed no significance.